On some leaf-miners (DipteraAgromyzidae) recently collected in ltaly (Bollettino di zoologia agraria e bachicoltura, 2024)
19 species of Agromyzidae collected in Italy in the past years directly on infested leafs or with Malaise trap are recorded. In the case of other 6 species the distrìbution has been specified. After this study the total number of Agromyzidae species in Italy is 222.
Keywords: new records; Agromyzidae; leaf-miners; Italy